Recent Advances of Electrocatalysts and Electrodes for Direct Formic Acid Fuel Cells: from Nano to Meter Scale Challenges - Li, Yang; Yao, Ming‑Shui; He, Yanping; Du, Shangfeng (Nano-Micro Letters, 2025)
Direct formic acid fuel cells are promising energy devices with advantages of low working temperature and high safety in fuel storage and transport. They have been expected to be a future power source for portable electronic devices. The technology has been developed rapidly to overcome the high cost and low power performance that hinder its practical application, which mainly originated from the slow reaction kinetics of the formic acid oxidation and complex mass transfer within the fuel cell electrodes. Here, we provide a comprehensive review of the progress around this technology, in particular for addressing multiscale challenges from catalytic mechanism understanding at the atomic scale, to catalyst design at the nanoscale, electrode structure at the micro scale and design at the millimeter scale, and finally to device fabrication at the meter scale. The gap between the highly active electrocatalysts and the poor electrode performance in practical devices is highlighted. Finally, perspectives and opportunities are proposed to potentially bridge this gap for further development of this technology. Highlights: 1 Comprehensive review of the progress in direct formic acid fuel cells from catalytic mechanisms to catalyst design, and to the electrode/device fabrication. 2 The gap between highly active formic acid oxidation catalysts and unsatisfactory device performance is highlighted. 3 Perspectives for catalyst and electrode design are discussed.